HELPING PEOPLE WITH VERY SEVERE COPD: FEASIBILITY STUDY OF A NOVEL COMMUNITY-BASED HOLISTIC INTERVENTION. Issue 1 (1st March 2014) - Kendall, M; Buckingham, S; Ferguson, S; Sheikh, A; Murray, SA; Boyd, K; Pinnock, H; MacNee, W; Worth, A; White, P
Abstract : Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of death worldwide. Research shows people with severe COPD have unmet needs, and the traditional cancer palliative care model is not appropriate. Aim(s) and method(s): To pilot and evaluate HELP-COPD - a community-based proactive holistic assessment of needs. The intervention comprised a home visit by a respiratory nurse, following discharge from hospital after an exacerbation, to discuss social/psychological/spiritual/physical needs, provide advice/information and make further referrals. A HELP_COPD Action Plan was completed and given to the patient and general practitioner. Follow-up included three phone calls over six months. Qualitative evaluation of HELP-COPD comprised interviews with participating patients, lay-carers and health professionals, alongside documentary analysis of completed action plans. Interviews were recorded, transcribed and entered into NVivo for thematic analysis. Results: 23 patients, from two hospitals, completed action plans. 31 interviews were completed. Patients were generally positive, openly discussing concerns and coping strategies in all domains. Professionals considered the intervention feasible and potentially valuable. Actions included facilitating discussion with their GP on palliative use of opiates, reinforcing referral to pulmonary rehabilitation and providing details of local voluntary services. However, fewer unmet needs were identified than expected, and some patients declined proffered services/information. Participants highlighted overlap with discharge planning and case management provided by community teams. Conclusion(s): HELP COPD was feasible and generally welcomed by patients. Fewer actions were identified than anticipated due to a combination of inappropriate timing, reluctance to accept social services, duplication by existing services and long-term adaptation reducing recognition of need and of the seriousness of the condition.